2014
DOI: 10.1111/lam.12369
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria inheritance is a key factor for tolerance to dehydration in wine yeast production

Abstract: In modern oenology, yeast starters are employed to inoculate grape juice, usually in the form of active dry yeast (ADY). The dehydration process implies stressful conditions that lead to oxidative damage. Other yeast species and interspecific hybrids other than Saccharomyces cerevisiae may be used to confer novel properties to the final product. However, these yeasts are usually more sensitive to drying. Understanding the causes of oxidative stress tolerance is therefore necessary for developing the use of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Has adaptation played a role in driving these incompatibilities? Although no direct links are proven, evolution of the mitochondrial genome and mito-nuclear epistasis has been linked to multiple phenotypes (Solieri et al 2008;Albertin et al 2013;Picazo et al 2014), including 37°C growth (Paliwal et al 2014, Wolters et al 2018, Leducq et al 2017, and deficiencies in mitochondrial DNA cause heat sensitivity (Zubko and Zubko 2014). Here, we show that mtDNA is important for evolution of heat and cold tolerance in distantly related species, caused by the accumulation of multiple small-to-medium effect changes and potentially mito-nuclear epistasis.…”
Section: Mitochondrial Dna and Yeast Evolutionmentioning
confidence: 79%
“…Has adaptation played a role in driving these incompatibilities? Although no direct links are proven, evolution of the mitochondrial genome and mito-nuclear epistasis has been linked to multiple phenotypes (Solieri et al 2008;Albertin et al 2013;Picazo et al 2014), including 37°C growth (Paliwal et al 2014, Wolters et al 2018, Leducq et al 2017, and deficiencies in mitochondrial DNA cause heat sensitivity (Zubko and Zubko 2014). Here, we show that mtDNA is important for evolution of heat and cold tolerance in distantly related species, caused by the accumulation of multiple small-to-medium effect changes and potentially mito-nuclear epistasis.…”
Section: Mitochondrial Dna and Yeast Evolutionmentioning
confidence: 79%
“…Different stress tolerances exist, even among Saccharomyces species of enological interest. Using hybrids, it has been proven that S. cerevisiae mitochondria better protect against dehydration than Saccharomyces uvarum mitochondria (Picazo et al 2015a). Therefore, the oxidative stress response is a potential target for wine yeast improvement, and using natural antioxidants like argan oil is a feasible way to improve biomass production (Gamero-Sandemetrio et al 2015).…”
Section: Ady Productionmentioning
confidence: 99%
“…The results showed that hybrid strain clones containing mtDNA of S. cerevisiae were more resistant to drying procedures than the clones containing S. uvarum mtDNA. The authors of this research concluded that the resistance of mtDNA to water loss is a very important factor in the survival of dehydrated yeast cells [37]. This study showed the importance of mitochondria and their role in the maintenance of cell viability during yeast dehydration, storage in the dry state, and rehydration/reactivation.…”
Section: Introductionmentioning
confidence: 61%